2016
DOI: 10.1016/j.watres.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of diclofenac in hybrid biofilm–activated sludge processes

Abstract: The biotransformation of diclofenac during wastewater treatment was investigated. Attached growth biomass from a carrier-filled compartment of a hybrid-MBBR at the wastewater treatment plant (WWTP) in Bad Ragaz, Switzerland was used to test the biotransformation. Laboratory-scale incubation experiments were performed with diclofenac and carriers and high-resolution LC–QTof-MS was implemented to monitor the biotransformation. Up to 20 diclofenac transformation products (TPs) were detected. Tentative structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(56 citation statements)
references
References 35 publications
4
47
2
3
Order By: Relevance
“…The sensitivity of microorganisms to this compound could be partly responsible for the harmful effects of DCF and/or DCF-containing mixtures on the microbial biodiversity in the AS. Jewell et al [56] revealed 88% removal of the initial concentration of DCF (1.6 µg L −1 ) in the influent of the full-scale WWTP during 10-day monitoring experiment and confirmed the formation of several by-products. In this study, significant differences in DCF removal were found between the bioaugmented assay AS1 and non-bioaugmented AS2.…”
Section: Pharmaceuticals Removal and Secondary Metabolites Formationmentioning
confidence: 87%
See 1 more Smart Citation
“…The sensitivity of microorganisms to this compound could be partly responsible for the harmful effects of DCF and/or DCF-containing mixtures on the microbial biodiversity in the AS. Jewell et al [56] revealed 88% removal of the initial concentration of DCF (1.6 µg L −1 ) in the influent of the full-scale WWTP during 10-day monitoring experiment and confirmed the formation of several by-products. In this study, significant differences in DCF removal were found between the bioaugmented assay AS1 and non-bioaugmented AS2.…”
Section: Pharmaceuticals Removal and Secondary Metabolites Formationmentioning
confidence: 87%
“…The accumulation of O-desmethylnaproxen, a key by-product of NPX degradation, identified e.g., for B. thuringiensis B1(2015b) [58], was excluded by the UHPLC MS/MS analysis. For DCF, 4-OH-DCF and lactam DCF are known as one of the most important initially formed secondary metabolites during microbial degradation [56]. The constant presence of 4-OH-DCF was confirmed in the AS1 assay using the UHPLC MS/MS with the highest value at t 21 .…”
Section: Pharmaceuticals Removal and Secondary Metabolites Formationmentioning
confidence: 88%
“…However, CBZ apparently biodegrades only in soils (Radke and Maier 2014 ; Li et al 2013 ). As the number of possible TPs is high for each IBU (Ferrando-Climent et al 2012 ; Vione et al 2011 ), DCF (Jewell et al 2016 ; Agüera et al 2005 ), and CBZ (Kosjek et al 2009 ), a subset of them was selected for inspection. The parent compounds, the selected TPs, and their relevant properties are listed in Tables 1 , 2 , and 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Due to the negative charge, sorption to the negatively loaded humic substances of the peat seems to be insignificant. The biotransformation of diclofenac is described as small [10], but mostly under oxic conditions [10,41]. Photodegradation, as a dominant process for the removal [42], is dependent on the pattern of soil cover by Phragmites australis which provides shadow on a brown soil surface.…”
Section: Dissipationmentioning
confidence: 99%